Tamanho de parcela e número de repetições para avaliar a massa verde de parte aérea de milheto - Burin, Cláudia (2015)
The present study aimed to determine the optimum plot size and number of repetitions to evaluate the fresh weight of aerial part of millet (Pennisetum glaucum (L). R. Brown) in evaluation times (Chapter I) and to determine the optimum plot size and number of repetitions to evaluate the fresh weight of aerial part of millet in times of sowing and cuts (Chapter II). Were conducted uniformity trials of 6m×4m (24m2), in the agricultural years 2012-2013 and 2013-2014, at the experimental area of the Crop Science Department of the Federal University of Santa Maria. Each trial was divided in 24 experimental units basic (UEB) with 1m×1m (1m2). The fresh weight of aerial part of plants was weighed in each UEB. At 52, 69 and 82 days after sowing were evaluated, respectively, 18, 6 and 18 trials, in the agricultural year 2012-2013 (Chapter I). In the agricultural year 2013-2014, there were three times of sowing and three fresh weight cuts in the first and third times of sowing, to evaluate the regrowth. In the second time of sowing was conducted a single cut (Chapter II). The plot size, for two agricultural years, was determined by the method of maximum curvature of the model coefficient of variation and the means compared, among evaluation times, among cuts and among times of sowing by Student s t test. The number of repetitions, for experiments on completely randomized and randomized block designs, in scenarios of combinations of i treatments (i=3, 4, ..., 50) and d minimal differences between treatments means to be detected as significant, 5% probability by Tukey test, expressed in percentage of the average of the experiment (d=10%, 12%, ..., 30%), was determined by iterative process until convergence. In the agricultural year 2012-2013, the optimum plot size to evaluate the fresh weight of aerial part of millet is 4.46m2, to the three evaluation times. To evaluate up to 50 treatments, in completely randomized and randomized block designs, four replications are sufficient to identify as significant at 5% probability, by Tukey test, differences between treatment means of 28.75% of the average experiment (Chapter I). In the agricultural year 2013-2014, the optimum plot size to evaluate the fresh weight of aerial part of millet is 4.97m2, to the three times of sowing and cuts. To evaluate up to 50 treatments, in completely randomized and randomized block designs, five replications are sufficient to identify as significant at 5% probability, by Tukey test, differences between treatment means of 28.66% of the average experiment (Chapter II).